Can the Caribbean localize its food system?: Evidence from biomass flow accounting. (15th February 2022) - Rahman, Shupa; Singh, Simron; McCordic, Cameron
Abstract: Small island economies are highly dependent on food imports. Self‐sufficiency through food localization is therefore often advocated. Can a small Caribbean island nation localize its food system? To answer this question, we conducted socio‐metabolic research on four Caribbean nations: Barbados, Dominica, Grenada, and Jamaica. Derived indicators from a diachronic biomass flow accounting from 1961 to 2019 suggest a declining trend in local food production for all cases. While in Barbados and Jamaica this decline already began in the 1960s, for Dominica and Grenada, this did not start until the late 1970s–1980s. The physical trade balance of biomass is similar across all cases: from net exporters at the start of the study period to net importers as countries developed, albeit at different time periods. By disaggregating biomass flow data to crop level, Barbados and Jamaica indicate a trend that is moving away from food localization, while Dominica and Grenada appear to be modestly moving toward localization in recent years. Given the many resource security challenges small island economies face, this study provides a biophysical perspective to the Caribbean's food security debate and questions the extent to which food localization is possible in a small island context, and whether other strategies are urgently needed.